DEVELOPMENT & VALIDATION OF A HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS DETERMINATION OF IRBESARTAN AND ITS RELATED IMPURITIES IN PHARMACEUTICAL TABLETS (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A novel isocratic reverse phase high performance liquid chromatographic (RP-HPLC) method was developed for the determination of purity of Irbesartan drug substance in bulk samples and its pharmaceutical dosage forms in the presence of its impurities. This method is capable of separating related impurities along with Irbesartan. This method can be also be used for the estimation of assay of Irbesartan in drug substance as well as in single tablet formulation. Two impurities were detected in drug sample by HPLC analysis. The chromatographic conditions were optimized using an impurity-spiked solution. MS and IR method was used for the identification of impurities. The structure of the impurities were confirmed as 2-Cyano-4'-bromomethyl biphenyl and 2-n-butyl-1, 3-diazaspiro [4, 4]-non-1-ene-4-one. The method was subsequently validated for the determination of Irbesartan and its related compounds, as per ICH guidelines, for accuracy, precision, linearity and range, selectivity, limit of detection, limit of quantification and robustness. The LOD for Irbesartan, Impurity 1 and Impurity 2 was found to be 18.51µg/ml or ppm, 16.033µg/ml or ppm and 16.069µg/ml or ppm respectively while LOQ was found to be 56.098µg/ml or ppm, 48.587µg/ml or ppm and 48.69µg/ml or ppm respectively.